The mechanical bond on carbon nanotubes: diameter-selective functionalization and effects on physical properties. Issue 17 (18th April 2016) - Martínez-Periñán, Emiliano; de Juan, Alberto; Pouillon, Yann; Schierl, Christoph; Strauss, Volker; Martín, Nazario; Rubio, Ángel; Guldi, Dirk M.; Lorenzo, Encarnación; Pérez, Emilio M.
Abstract : The formation of MINTs is diameter-selective and produces distinct effects on properties of the SWNTs, clearly different from supramolecular references. Abstract : We describe the functionalization of SWNTs enriched in (6, 5) chirality with electron donating macrocycles to yield rotaxane-type mechanically interlocked carbon nanotubes (MINTs). Investigations by means of electron microscopy and control experiments corroborated the interlocked nature of the MINTs. A comprehensive characterization of the MINTs through UV-vis-NIR, Raman, fluorescence, transient absorption spectroscopy, cyclic voltammetry, and chronoamperometry was carried out. Analyses of the spectroscopic data reveal that the MINT-forming reaction proceeds with diameter selectivity, favoring functionalization of (6, 5) SWNTs rather than larger (7, 6) SWNTs. In the ground state, we found a lack of significant charge-transfer interactions between the electron donor exTTF and the SWNTs. Upon photoexcitation, efficient charge-transfer between the electron donating exTTF macrocycles and SWNTs was demonstrated. As a complement, we established significantly different charge-transfer rate constants and diffusion coefficients for MINTs and the supramolecular models, which confirms the fundamentally different type of interactions between exTTF and SWNTs in the presence or absence of the mechanical bond. Molecular mechanics and DFT calculations support the experimental findings.